Feeding Habits of Marsela Fish (Parachromis managuensis) In Penjalin Reservoir Brebes, Central Java - Kresnasari, Dewi; Darajati, Anggun Dwita (Universitas PGRI Semarang, 2020)
Abstract. The presence of introduced fish populations in the Penjalin Reservoir is increasing, one of the dominant ones being caught is Marsela (Parachromis managuensis). It is feared that this fish population will continue to increase and will have a negative impact on other organisms, especially native fish communities. This study aims to determine the eating habits of Marsela fish, the composition of the type of food and its relationship to the abundance of plankton in the waters. This research was conducted in September-October 2018. The method used was CPUE with a sampling technique that is Simple Random Sampling. Sampling of fish in one day is done 6 times, namely at 05:00, 11:00, 17:30, 21:00, 00:00, and 03:00. Fish samples obtained are then grouped according to length and then an analysis of the contents of the stomach. The results showed that in the Penjalin Reservoir the percentage of phytoplankton presence was 96% with the highest abundance found in the Bacillariophyta group. Marsela is an omnivorous fish with popular foods are Chlorophyta and Charophyta. However, in adulthood Marsela fish also eat animals.Keywords: Marsela Fish (Parachromis managuensis), Fish Eating Habits, Penjalin Reservoir